If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90x + 50 = 100x Reorder the terms: 50 + 90x = 100x Solving 50 + 90x = 100x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-100x' to each side of the equation. 50 + 90x + -100x = 100x + -100x Combine like terms: 90x + -100x = -10x 50 + -10x = 100x + -100x Combine like terms: 100x + -100x = 0 50 + -10x = 0 Add '-50' to each side of the equation. 50 + -50 + -10x = 0 + -50 Combine like terms: 50 + -50 = 0 0 + -10x = 0 + -50 -10x = 0 + -50 Combine like terms: 0 + -50 = -50 -10x = -50 Divide each side by '-10'. x = 5 Simplifying x = 5
| 4(5-x)=-4.9+2.1(6x) | | 5(x+1)-2(x-1)=12 | | -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) |